Konseling Individu Berbasis Terapi Realitas: Strategi Meningkatkan Asertivitas Pada Gen-Z Di Era Digital - Rojabiah, Harirotul Janiah; Mahmudah, Mahmudah; Khaudli, Imam (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
In today’s fast-paced digital era, Generation Z faces unique challenges in developing assertiveness, namely the ability to express oneself effectively while respecting the rights of others. This study aims to examine the effectiveness of applying reality therapy techniques in individual counseling to enhance the assertiveness of Generation Z in the digital age. This research employed a qualitative approach with Generation Z participants who engaged in individual counseling sessions using reality therapy. Data collection techniques included in-depth interviews, nonverbal behavior observation, personality inventory, assertiveness scale, and clients’ daily journals. The data were analyzed thematically to explore the counseling process and behavioral changes in assertiveness. The findings reveal that reality therapy effectively improves Generation Z’s assertiveness, indicated by better communication skills, the ability to set interpersonal boundaries, and constructive conflict management. Key factors contributing to success include personal responsibility awareness and social support. This study highlights the relevance of integrating reality therapy into counseling programs to strengthen assertive skills, psychological resilience, and social adaptability among Generation Z in the digital era.